Design Of Bedside Monitor Based On Microcontroller - Bambang Guruh Irianto; Agus Susilo Wibowo; Dwi Herry Andayani (JURNAL INFOTEL, 2019)
A Bedside monitor is the equipment used to monitor patient condition through some parameters that need sustainable monitoring so that the patient condition is always monitored. This research is monitored by 5 parameters namely heart signal, heart rate, temperature, respiration and SPO2. This research applies quasi experimental design. The free variable is an ECG phantom or human, and the dependent variable is a bedside monitor. The research instruments are a calibration equipment of ECG signal, temperature, and respiration. The result of the heart signal lead 2 is not different from the standard and the result of the heart rate lead has uncertainty (probability) 0 for Lead 2; which is still under the tolerance number (0.5). The results of the temperature measurement of 5 samples with 5 measurements show that there are 3 samples which have standard deviation and 0 (zero) uncertainty, whereas 2 samples have 0.76 (higher than 0.5) uncertainty. This condition is influenced by the patient movements, so the sensor attached on the patient-body does not fit with the standard installation. The respiration measurement results have an accuracy of 98%, while the SPO2 results have a standard deviation and uncertainty below 5% after being compared with the standard calculations. Here are the details: standard deviation 0.894427; 0.547723; 0.44; Probability 0.4; 0.244949; 0.2 and 0.2. Overall, it can be concluded that The Design of Bedside Monitor Based on Microcontroller is feasible and the measurement result of heart signal Lead 2, heart rate, temperature, respiration, SPO2 can be presented on a PC.